UPAYA MENINGKATKAN HASIL BELAJAR IPA DAN BAHASA INDONESIA SISWA KELAS V A MELALUI MODEL PEMBELAJARAN CTL (CONTEXTUAL TEACHING AND LEARNING) SD NEGERI 007 BAGAN BESAR - Raihan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This study aimed to describe learning outcomes through the use of map media. The subjects were students of class 007 VA SD Negeri Besar Bagan for great learning results. This research is a classroom action research, conducted over two cycles. Data was collected using observation techniques and teacher and student achievement tests. This research applied the CTL learning model. The results showed that Indonesian and Science learning outcomes increased, characterized by an increase in student mastery of the learning material to 60% and above. In the second cycle, 22 out of 25 students (85%) achieved this for science subjects. In Indonesian subjects, 23 students out of 25 (92%) achieved this. Student mastery of the learning material below 60% was observed in three students out of 25 (15%) in science subjects, and in two students out of 25 (8%) in Indonesian subjects. Based on this, it can be concluded that the application of the CTL model can improve science and Indonesian learning outcomes.